A plague of rat and rubbervines : - Baskin, Yvonne (Island Press, 2003)
A Plague of Rats and Rubbervines, widely published science writer Yvonne Baskin draws on extensive research to provide an engaging and authoritative overview of the problem of harmful invasive alien species